Spider mites associated to soybean in Rio Grande do Sul, Brazil - Roggia, Samuel; Guedes, Jerson Vanderlei Carús; Kuss, Rejane Cristina Roppa; Arnemann, Jonas André; Návia, Denise (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to study the occurrence and geographic distribution of phytophagous mites associated to soybean in Rio Grande do Sul, Brazil. Samplings were performed from January to May 2005 on genetically modified soybean (glyphosate-tolerant) crops, in 27 municipalities of six regions – Alto Vale do Uruguai, Campanha, Depressão Central, Planalto Médio, Missões and Serra do Sudeste. Five phytophagous mite species belonging to the family Tetranychidae – Mononychellus planki, Tetranychus desertorum, T. gigas, T. ludeni and T. urticae – occurred in 21, 12, 5, 3 and 14 municipalities, respectively. A map of Rio Grande do Sul with the geographic distribution of each species is presented, as well as an illustrated dichotomous key to help the identification of the spider mites found.